Correlation between CD4 T lymphocyte and Candida Species Counts In Oral Candidiasis Patients with HIV / AIDS - Dwi Murtiastutik1 , Cita Rosita Sigit Prakoswa2 , Indah Setyawati Tantular 3, Evy Ervianti1 , Afif N (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Candida sp. is the most common opportunistic pathogen found during the development ofHuman immunodeficiency virus (HIV) & Acquired immune deficiency syndrome (AIDS) disease. Theclinical severity of oral candidiasis and the prevalence profile of Candida species reflect immunologicalchanges in HIV / AIDS patients. Objective: Evaluating the relationship between CD4 T lymphocyte cellscounts and the number of Candida species. Methods: A cross-sectional analytical study was carried outat Dr. Soetomo, Surabaya, Indonesia. For identification of Candida species, culture was carried out onChromagar media followed by culture with vitek 2. Results: There were 114 study subjects who weredivided into three groups based on the number of CD4 T lymphocyte cells, with 158 isolates of Candidaspecies growing in culture. The highest number of Candida species was Candida albicans with a total of 107isolates (67.7%). Candida non-albicans were 51 isolates (32.3%). Statistical test results showed a significantcorrelation between the number of CD4 T lymphocyte cells and the number of Candida species (p <0.001).Conclusion: The decrease in CD4 lymphocyte cell counts is influenced by various types of Candida sp. inoral candidiasis patients.